Dynamics of a vapor bubble inside a vertical rigid cylinder with and without a deposit rib (Archives of Mechanics - Test, 2016)
In this paper, the dynamics of a vapour bubble generated due to local energy input inside a vertical rigid cylinder and in the absence of buoyancy forces was investigated. Different ratios of the diameter of the rigid cylinder up to the maximum radius of the bubble were considered. The boundary integral equation method was employed for numerical simulation of the problem. The results show that during the collapse phase of the bubble inside a vertical rigid cylinder, two liquid micro jets are developed on the top and bottom sides of the vapor bubble and are directed inward. It is found that by increasing the ratio of the cylinder diameter to the maximum radius of the bubble, the rate of the growth and collapse phases of the bubble increases and the lifetime of the bubble decreases. The results also show that an increase in the thickness of the deposit rib inside a vertical rigid cylinder slightly decreases the lifetime of the bubble.